Analysis of Sexual Violence Behavior in the Islamic Boarding Schools (Analysis Study of Erving Goffman's Dramaturgy Theory) - Said Ali Uraidhi; Muhammad Farhan Alfarisy; Ravi Rajesta Rasyid (Social Issues Quarterly, 2023)
The cases of sexual violence against teenagers are increasing day by day. Cases of sexual harassment in both physical and virtual spaces have received attention in the last five years. The locus of sexual violence can be anywhere, especially in Islamic boarding schools which should be safe from all types and forms of violence. This study aims to determine how sexual violence in boarding schools affects society's lives. The data collection method includes qualitative descriptive methods that rely on observation and literature review. Based on the results of the study, the actors in role play have the following characteristics: (1) In the family and institution, the actors tend to be better and more polite by highlighting religious characteristics. (2) Actors do not create a large gap between themselves and their listeners. Although they have many friends, they keep their sexual activities secret. (3) Actors impression management, which involves acting more formally and engaging in more polite activities, is aimed at building associative relationships. (4) The third world/the outside world observes the performance and keeps it a secret. (5) The separation of actors from their respective roles is due to feelings of guilt and regret towards God, the people they love, and their friends.